2007
DOI: 10.1108/00483480710752803
|View full text |Cite
|
Sign up to set email alerts
|

Productivity improvements: understand the workforce perceptions of productivity first

Abstract: PurposeTo establish the differences between the perceptions of white‐collar managers and blue‐collar workers with respect to the factors that affect construction labour productivity, and to show that integrating the differences could lead to productivity improvements.Design/methodology/approachA questionnaire survey administered to a purposive sample of 400 project managers and a convenience sample of 152 construction workers, eliciting current trends of their perceptions towards 59 factors that were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
0
32
0
3
Order By: Relevance
“…The results revealed that, control and quality requirements are the most important factors for project managers and craft workers, respectively. In this paper, a similar research to Chan and Kaka [10] was conducted for Turkey. For this purpose, via a questionnaire 37 factors grouped under 4 categories were evaluated by project managers and craft workers, and statistically analyzed.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…The results revealed that, control and quality requirements are the most important factors for project managers and craft workers, respectively. In this paper, a similar research to Chan and Kaka [10] was conducted for Turkey. For this purpose, via a questionnaire 37 factors grouped under 4 categories were evaluated by project managers and craft workers, and statistically analyzed.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Therefore in this study both of the participant groups emphasized on similar factors which were lack of construction equipment, materials and tools, and engineering drawings [7]. Finally, Chan and Kaka [10] conducted a research in UK to compare the labor productivity perspectives of project managers and craft workers. Similar to other studies a questionnaire was applied to both of these participant groups.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The research interest in the application of concept of worker involvement, integration of perspectives of workers and managers on productivity in the construction industry is still at the nascent stage since Chan (2006Chan ( , 2007 rekindled it to the research agenda. The possibility of widening the worker integration to encompass social relationship is also investigated.…”
Section: Key Theoretical Concepts Under Investigationmentioning
confidence: 99%
“…These studies are separately looking into two aspects of productivity; namely areas where productivity improvement is possible (eg. Arditi,1985; Arditi and Mochtar,1996) and productivity improvement techniques (Cottrell, 2006;Chan and Kaka, 2007;Han et al2008, Minchin et al2008. It is striking to note that follow up studies have not been conducted to empirically verify the validity of claims and promises made in productivity improvement studies.…”
Section: Types Of Research Objectsmentioning
confidence: 99%
See 1 more Smart Citation